2017
DOI: 10.1007/s11764-017-0648-6
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between self-reported and register-based cardiovascular events among Danish breast cancer survivors

Abstract: Determining how cancer treatments affect the risk of cardiovascular morbidities is essential, and the development of high-quality methods for collecting such data is critical. While self-reported data are adequate for assessing the presence of any CVD condition, medical record review will yield higher quality data on specific CVD conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Our results show that earlier reports can be confirmed in a different health care system. In a validation study with 357 Danish breast cancer patients who conducted a telephone-interview on cardiovascular diseases (CVD) [ 14 ], the authors found a high accuracy (94%) for reporting the absence of CVD, comparing self-reports and diagnostic codes from the Danish National Patient Register. This is in line with our and previous studies, who showed a high accuracy of recall for participants who did not report a CVD [ 15 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results show that earlier reports can be confirmed in a different health care system. In a validation study with 357 Danish breast cancer patients who conducted a telephone-interview on cardiovascular diseases (CVD) [ 14 ], the authors found a high accuracy (94%) for reporting the absence of CVD, comparing self-reports and diagnostic codes from the Danish National Patient Register. This is in line with our and previous studies, who showed a high accuracy of recall for participants who did not report a CVD [ 15 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Complex diagnostic criteria and closely related cardiac symptoms could make it difficult for patients to report specific diagnoses accurately. Combining closely related cardiac diseases (angina pectoris and myocardial infarction) may increase the validity of self-reports [ 14 , 17 ]. Accordingly, in our validation study single cardiac diseases were combined to a comprehensive item.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study to report that the agreement between self-reported and provider-reported comorbidities among older hospitalized patients with heart failure is generally poor. Though a direct comparison was not performed, the agreements of hypertension, diabetes mellitus, COPD, and coronary artery disease were numerically lower in patients with heart failure compared with the general elderly population, [1][2][3] patients with cancer, [10][11][12] and patients with chronic kidney disease, 13,14 which may be due to a variety of reasons. As the FRAGILE-HF study focused on older patients with heart failure, the patient population in this study included older patients, and age is a strong predictor of disagreement between patient reports and medical records regarding the presence or absence of comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The understanding and recognition of one's own comorbidities is an essential and fundamental aspect of patient education. 7 Studies on the general population, [1][2][3]8,9 patients with cancer, [10][11][12] and patients with chronic kidney disease 13,14 have reported that patients do not necessarily recognize their own comorbid conditions that are recorded in their medical records and that the agreement between self-reported and provider-reported comorbidities is generally poor. The accuracy of self-reported comorbidities among patients with heart failure has not been reported.…”
Section: Introductionmentioning
confidence: 99%